"Jag har inte riktigt tålamod att slå upp i ordboken" Om översättares inställning till ordböcker i ljuset av tänka-högt-protokoll - Virtanen, Pia (Nordiske Studier i Leksikografi, 1997)
The aim of this paper is to study think-aloud protocols of translation in order to find out what is the attitude of translators towards their dictionaries. Attention was paid to the dictionary users conunents on their use of dictionaries and what these conunents tell about their attitude towards dictionaries in general, towards individual dictionaries and towards the information dictionaries give them. Dictionary users appear to take a negative rather than a positive attitude towards dictionaries. The negative, sceptical attitude dominates especially with dictionaries the user does not know well or has not used before, whereas the positive attitudes and expectations seem to be connected with familiar dictionaries which the user a1ready knows he/she can trust. It also appears that those who do not use dictionaries very much have an overall negative attitude, while the "heavy" users have a neutral rather than a positive attitude towards dictionaries and the use of them.